Obstacles and Challenges to Gender Parity. Political Violence, Electoral System and Interculturalism - Laura Albaine (Íconos)
This study is a contribution to the debate about the adoption of gender parity policies in Latin America analyzing particular obstacles and challenges related to the implementation of this principle. Electoral systems tend to either optimize or reduce the impact of such gender parity measures. As well as with quotas, the size of the electoral district and the kind of electoral list system are the two variables that most influence the effective implementation of these measures. At the same time, the socio-cultural context also influences the process of implementation of gender parity measures. In patriarchal societies –with high levels of gender-based violence– electoral processes are often characterized by gender-based harassment and political violence, one of the greatest obstacles for increasing women’s political participation. These situations are further complicated in societies which are also characterized by ethnic and cultural diversity, presenting the challenge of including women who are also discriminated against for their ethno-cultural identity.